Preconditioning With Levosimendan Before Implantation of Left Ventricular Assist Devices. Issue 3 (22nd October 2013) - Theiss, Hans D.; Grabmaier, Ulrich; Kreissl, Nicole; Hagl, Christian; Steinbeck, Gerhard; Sodian, Ralf; Franz, Wolfgang‐M.; Kaczmarek, Ingo
Abstract In this retrospective study, we investigated the impact of preconditioning of the right ventricle with the calcium sensitizer levosimendan immediately before left ventricular assist device (LVAD) implantation on outcome and survival. Nine consecutive LVAD patients (seven suffering from dilative cardiomyopathy and two from ischemic cardiomyopathy) with echocardiographic and invasive evidence of right heart insufficiency received levosimendan with 0.1 μg/kg body weight/min for 24 h before implantation of the assist device (seven HeartWare and two Jarvik 2000). Administration of levosimendan was safe and had not to be discontinued in any patient. We observed no relevant side effects. Twelve‐month survival after implantation of the LVAD was 89% representing a superior outcome compared with the fifth INTERMACS registry data with 75% survival. Two temporary extracorporeal membrane‐oxygenation implantations were necessary due to intraoperative right ventricular dysfunction. Only one patient died 5 weeks after LVAD implantation of multiorgan failure, five patients were successfully transplanted, and three patients underwent LVAD implantation for destination therapy. Levosimendan might improve clinical outcome and survival when used as pretreatment in patients with right heart insufficiency prior to LVAD implantation. However, we recommend a larger controlled trial in the future to confirm our preliminary results.